Relief of Urinary Urgency, Hesitancy, and Male Pelvic Pain with Pulse Radiofrequency Ablation of the Pudendal Nerve: A Case Presentation - Christopher Bui; Sanjog Pangarkar; Scott I. Zeitlin (Case Reports in Urology)
Background and Aims. This report demonstrates the utility of a pudendal nerve block by pulsed radiofrequency ablation (RFA) for the treatment of male pelvic pain and urinary urgency and hesitancy. Methods. The patient is an 86-year-old gentleman with a 30-year history of urinary hesitancy and urgency. The patient also had pain in the area of the perineum but considered it a secondary issue. The patient was seen by a number of specialists, tried various medications, and underwent a variety of procedures to no avail. Therefore, the patient underwent a pulsed RFA of the pudendal nerve. Results. The patient underwent a pulsed RFA of the pudendal nerve; the patient reported marked improvement in his pelvic pain as well as a drastic reduction in his urinary urgency and hesitancy. Conclusion. Urinary urgency and hesitancy and male pelvic pain are some of the most common symptoms affecting men. Pudendal nerve block by pulsed RFA is an effective treatment of pelvic pain. It may also hold some therapeutic value in the treatment of urinary urgency and hesitancy as our case demonstrated. Further studies are needed to help clarify both the anatomy of the pelvis as well as if pudendal blocks are effective in treating more than pelvic pain.